1829-1821: RIEGO MUEVE MADRID. NUEVAS BRISAS EN EL VIEJO REPERTORIO DE ACCION COLECTIVA EN LA ESPAÑA DEL SIGLO XIX (Res Publica. Revista de Historia de las Ideas Políticas, 2009)
Starting from the idea of «collective action repertoire» as a cultural artefact (Charles Tilly), this paper focuses on the mobilizations that followed the dissolution of De la Isla Army and the removal of Riego as Field Marshal of Aragon, in Madrid during 1820-21. Whithout denying the persistence of traditional ways of protest, this work intends to enrich the common view about the collective action in Spain during the XIXth century, as well as emphasizing some distinctive features of the new repertoire: the decrease of violence, the political nature of demands, the role of Patriotic Societies and the spread of mobilizations.